ENTROPY AND ITS ROLE IN THE DIGITAL TRANSFORMATION OF BUSINESS PROCESSES OF THE ENTERPRISE - RIEPINA, Inna; TEPLIUK, Mariia; DZIUBA, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the influence of entropy on the digital transformation of the enterprise's business processes, which is an important topic in today's conditions of globalization and rapid technological development. The introduction of new digital technologies leads to an increase in uncertainty and chaos in organizational structures, which complicates the management of business processes. The authors noted that digitalization completely changes the way tasks are performed and the structure of processes at the enterprise, which in turn can lead to a change in the roles and responsibilities of employees.It is justified that any changes in the enterprise automatically create uncertainty and form the basis for resistance to changes. It has been proven that when an enterprise implements new technologies, such as: automation, artificial intelligence, or the Internet of Things (IoT), it faces the need to integrate relevant technologies into the already existing business processes of the enterprise, which can become de stimulators of the development of economic entities. The main focus is on the analysis of factors that contribute to the increase of entropy, such as the increase in the volume of information, inefficient data flows and the growth of cyber threats. The article also considers possible ways to reduce entropy, including reengineering business processes and using modern data management technologies.The authors emphasize the need for further research for a deeper understanding of the specific risks and opportunities associated with digital transformation, which will contribute to the successful development of enterprises in turbulent market conditions. Special attention is paid to the importance of entropy management to ensure the stability and competitiveness of enterprises. The authors emphasize the need for further research for a deeper understanding of the specific risks and opportunities associated with digital transformation, which will contribute to the successful development of enterprises in turbulent market conditions. The increase in entropy in the process of digitization is a natural consequence of the complexity and uncertainty associated with the introduction of new technologies and processes, so in order to successfully manage these challenges, enterprises must actively work on reducing the level of entropy through standardization, integration and clear communication of changes in the organizational structure.
Keywords: entropy; digital transformation; business processes; data management; cyber threats; reengineering; organizational structure; innovative technologies; globalization development